2021
DOI: 10.9758/cpn.2021.19.3.572
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive Therapy for Parkinson's Disease with Depression and Neuroleptic Malignant Syndrome: A Case Report

Abstract: Parkinson's disease is often complicated by psychiatric symptoms. Psychiatrists are caught in a dilemma between such symptoms and physical treatment since Parkinson's disease sometimes shows treatment resistance based on pharmacological treatment-induced dopamine dysfunction. Here, we report on a 64-year-old woman with a 15-year history of Parkinson's disease with stage IV severity based on the Hoehn and Yahr scale. She was admitted to our hospital with a diagnosis of major depressive disorder with psychotic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The publications examined in this systematic review delineate ECT as an effective intervention for symptoms associated with various movement disorders. Several studies confirmed a positive relationship between this therapy and PD [31][32][33][34][35][36]. After the sixth and seventh weeks, ECT significantly improved psychiatric, motor, and major depressive symptoms among PD patients [31].…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…The publications examined in this systematic review delineate ECT as an effective intervention for symptoms associated with various movement disorders. Several studies confirmed a positive relationship between this therapy and PD [31][32][33][34][35][36]. After the sixth and seventh weeks, ECT significantly improved psychiatric, motor, and major depressive symptoms among PD patients [31].…”
Section: Discussionmentioning
confidence: 78%
“…This effect depicts the therapy as a possible complementary intervention for treating and managing PD symptoms. Besides, ECT has been reported to reduce the symptoms of depression and malignant syndrome among PD patients [32]. Depression and malignant syndrome are critical symptoms of PD that cause adverse health implications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations